A reference data model of a metadata registry preserving semantics and representations of data elements - Löpprich, Martin; Jones, Jennifer; Meinecke, Marie-Claire; Goldschmidt, Hartmut; Knaup-Gregori, Petra (E-Health - for continuity of care, 2014)
Integration and analysis of clinical data collected in multiple data sources over a long period of time is a major challenge even when data warehouses and metadata registries are used. Since most metadata registries focus on describing data elements to establish domain consistent data definition and providing item libraries, hierarchical and temporal dependencies cannot be mapped. Therefore we developed and validated a reference data model, based on ISO/IEC 11179, which allows revision and branching control of conceptually similar data elements with heterogeneous definitions and representations.
Gesehen am 16.02.2021